On the relation between inward pointing velocity conditions - Lopes, Sofia Oliveira (2011)
Inward pointing velocity conditions are important in the study of whether trajectories remain within sets (the so-called invariance or viability) and also to establish constraint qualifications (CQ) under which necessary conditions of optimality for control problem can be guaranteed to be nondegenerate NCO or normal. In our research on nondegenerate NCO we have studied different types of CQs in the form of inward pointing velocity (IPV) conditions, and, in particular, in which situation one type implies other type of IPV. Such findings are reported in the article.